THE APPLICATION OF THE COLOR-CODED TEXT OF SURAH ASH-SHAMS TO ENHANCE STUDENTS' VOCABULARY ANALYSIS (Karya Ilmiah Mahasiswa (KIMA), 2024)
Methods and materials that are suitable for student circumstances are required to fulfill learning objectives, especially in ELT. Thus, students will put what they have learned into practice so that the learning process can be carried out well. This study was conducted to determine the effect of the color-coded text of surah Ash-Shams in improving students' vocabulary analysis. This research used a quantitative method with a Pre-Experimental design. The population of this research was the grade seventh Junior Highschool and consisted of 10 students. the results of this research showed that students' vocabulary analysis has improved by 42,65% from their starting point. Students also gave positive responses for the usage of color-coded text in Surah Ash-Shams. The students agreed that the color-coded text could ease them to distinguish the word classes. Therefore, it is suggested to employ the color-coded text of surah Ash-Shams or other surahs in the Holy Quran to improve the vocabulary analysis.